2022
DOI: 10.1177/08853282221085801
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alkyl chain length of (R)-3-Hydroxybutyric alkyl ester on antibacterial activity and its antibacterial mechanism

Abstract: This work describes the relationship between the antibacterial activity and the ester chain length (C1-C8) of ( R)-3-Hydroxybutyric (( R)-3-HB) alkyl esters that synthesized from ( R)-3-HB acid (( R)-3-HBA) by esterification reaction. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) decrease as the length of the ( R)-3-HB alkyl ester chain increases from 1 to 6, but ( R)-3-HB-C7 and ( R)-3-HB-C8 have their own rules for different microorganisms. Among them, the ( R)-3HB-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Similar results were observed with nylon-3 copolymers which decreased the MIC of azoles and AmB against some selected fungi, highlighting the potential of combination therapy (Rank et al, 2017). A study of aliphatic polyesters found that hydrophobic interaction induced the damage of fungal cell walls and membranes (Cheng et al, 2022). Mohamed et al (2015) highlighted the antimicrobial activity of cations by demonstrating that a higher degree of quaternization and glutaraldehyde cross-linking of the hydrogel resulted in a strengthened positive charge and more antibacterial activity.…”
Section: Systems Based On the Innate Antifungal Activity Of Polymerssupporting
confidence: 54%
See 1 more Smart Citation
“…Similar results were observed with nylon-3 copolymers which decreased the MIC of azoles and AmB against some selected fungi, highlighting the potential of combination therapy (Rank et al, 2017). A study of aliphatic polyesters found that hydrophobic interaction induced the damage of fungal cell walls and membranes (Cheng et al, 2022). Mohamed et al (2015) highlighted the antimicrobial activity of cations by demonstrating that a higher degree of quaternization and glutaraldehyde cross-linking of the hydrogel resulted in a strengthened positive charge and more antibacterial activity.…”
Section: Systems Based On the Innate Antifungal Activity Of Polymerssupporting
confidence: 54%
“…Similar results were observed with nylon-3 copolymers which decreased the MIC of azoles and AmB against some selected fungi, highlighting the potential of combination therapy ( Rank et al., 2017 ). A study of aliphatic polyesters found that hydrophobic interaction induced the damage of fungal cell walls and membranes ( Cheng et al., 2022 ). Mohamed et al.…”
Section: Polymer-based Strategies In Fungal Disease Treatmentmentioning
confidence: 99%
“…Not all PHAs possess antimicrobial or antiviral activity. The possible mechanisms of biocontrol activity can be related to the destruction of the microbial wall/membrane and the leakage of intracellular contents and changes in transmembrane potential [38,39]. The antimicrobial properties of PHAs are believed to be related to their monomers-hydroxylsubstituted fatty acids, which act as anionic surfactants.…”
Section: Antagonistic Activity Of Phas In Vitro Against Penicillium E...mentioning
confidence: 99%
“…flavescens D5 strain as biocontrol agents, three treatments of apple fruits were proposed: combined inoculation of PHA and the phytopathogen P. expansum, preventive treatment of PHA 24 h before inoculation of the phytopathogen, and therapeutic treatment with PHA 24 h after Not all PHAs possess antimicrobial or antiviral activity. The possible mechanisms of biocontrol activity can be related to the destruction of the microbial wall/membrane and the leakage of intracellular contents and changes in transmembrane potential [38,39]. The antimicrobial properties of PHAs are believed to be related to their monomers-hydroxylsubstituted fatty acids, which act as anionic surfactants.…”
Section: Evaluation Of the Possibility Of Using Phas As Biocontrol Ag...mentioning
confidence: 99%